Pencegahan Kekerasan Seksual dikalangan Mahasiswa Melalui Penyelenggaraan Pendidikan Karakter - Agista Saffa; Hanop Hanop; Reza Mauldy Raharja, M.Pd. (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to provide important understanding about sexual education among students, as well as with the help of the application of character education that will shape student awareness about sexual violence. This case of sexual harassment among students is indeed a very important event and needs firm handling and prevention. This study also provides a reference for students who have experienced sexual violence so that they are not afraid to report to the authorities. Indonesian President Joko Widodo passed Law Number 12 of 2022 on May 9, 2022 which discusses the Criminal Act of Sexual Violence. In particular, the Minister of Education, Culture, Research, and Technology has issued Regulation Number 30 of 2021 concerning the Prevention of Violence in Higher Education Environment (PPKS), with its implementation scheduled for August 31, 2021. This also shows that the government is not ignoring the problem of sexual violence. This study used a qualitative approach method that applied documentary research, observation and interviews were used.